ApoE Influences the Blood-Brain Barrier Through the NF-κB/MMP-9 Pathway After Traumatic Brain Injury - Zhipeng Teng (Nature Portfolio, 2017)
Abstract Apolipoprotein E (ApoE), encoded by the ApoE gene (APOE), influences the outcomes of traumatic brain injury (TBI), but the mechanism remains unclear. The present study aimed to investigate the effects of different ApoEs on the outcome of TBI and to explore the possible mechanisms. Controlled cortical impact (CCI) was performed on APOEε3 (E3) and APOEε4 (E4) transgenic mice, APOE-KO (KO) mice, and wild type (WT) mice to construct an in vivo TBI model. Neurological deficits, blood brain barrier (BBB) permeability and brain edema were detected at days 1, 3, and 7 after TBI. The results revealed no significant differences among the four groups at day 1 or day 3 after injury, but more severe deficits were found in E4 and KO mice than in E3 and WT mice. Furthermore, a significant loss of tight junction proteins was observed in E4 and KO mice compared with E3 and WT mice at day 7. Additionally, more expression and activation of NF-κB and MMP-9 were found in E4 mice compared with E3 mice. Different ApoEs had distinct effects on neuro-function and BBB integrity after TBI. ApoE3, but not E4, might inhibit the NF-κB/MMP-9 pathway to alleviate BBB disruption and improve TBI outcomes.